Dampak Covid-19 Terhadap Lulusan Sekolah Menengah Kejuruan Pada Bidang Teknik Pemesinan di Dunia Kerja - Restu Fazar Febrianto; Elfan Arya Rakha; Rizky Adi Zuliansah; Risma Aprillia; Ahmad Solehudin; Rizal Zayis Firdaus; Rama Wijaya Abdul Rozak; Ariyano Ariyano (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
This study aims to provide an overview of the suitability of machining engineering majors in the world of work. When the Covid-19 case is on the increase, especially in Indonesia, many graduates of vocational high schools have difficulty finding jobs according to the majors they are interested in, especially in the field of machining engineering expertise. This research method uses descriptive quantitative methods with field data obtained from the results of questionnaires distributed to vocational high school students in the field of machining engineering expertise so that 33 respondents can be analyzed. The results of the study show that there is suitability and incompatibility in finding work due to the impact of Covid-19, factors that can cause this such as students' lack of understanding of distance learning when affected by the Covid-19 outbreak and remote practicum which hinders the growth of students' competence that should be obtained to enter the world of work. In addition, the lack of information related to the world of work was also felt by students when the Covid-19 outbreak attacked Indonesia. Therefore, this research was conducted to find out how suitable graduates of vocational high schools are in finding jobs and in accordance with what they are interested in in their areas of expertise